Antecedents of Information Technology-Based Risky Investment - Rika Permata Sari; Willy Abdillah; Erni Hendrawaty (The Indonesia Capital Market Institute, 2019)
Purpose- This study examines the effect of emotional intelligence, the locus of control, and risk aversion on intention to risky investment with financial literacy as moderating effect. Methods- This study uses 98 investors distributed by online questionnaire. Data examined using Partial Least Square (PLS) technique. Finding- The results show that the emotional intelligence, the locus of control have a positive effect and risk aversion and financial literacy have a negative effect on intention to a risky investment. However, there is no moderating effect of financial literacy on those direct effects. Implication- The implication for stakeholder and further research are discussed